Personal Sovereignty in Adolescents and Youth from Armenia, China, and Russia - Sofya K. Nartova-Bochaver; Anna Hakobjanyan; Svetlana Harutyunyan; Narine Khachatryan; Michael S. Wu (Psychology in Russia: State of Art, 2018)
Background. In today’s hectic civilization, it is very important for a person to maintain personal boundaries which help him or her keep his/her identity. Personal sovereignty (PS) is a trait that demonstrates the extent to which a person’s empirical Self is respected by his/her social environment. Whereas the genesis and correlations system of personal sovereignty in proximal relationships have been investigated widely, little is known about whether they are culturally sensitive or not. Objective. In this study, we aimed to investigate the patterns and genesis of personal sovereignty in relation to age and gender, by comparing individuals from Armenian, Chinese, and Russian cultures. Our sample consisted of 780 respondents, of whom 223 were from Armenia, 277 from China, and 280 from Russia; 367 were adolescents (Mage=13) and 413 were youth (Mage=21); there were 361 males and 419 females. Method. The “Personal Sovereignty Questionnaire–2010” was used. Results. The results suggest that culture, age, and gender all impact on the sense of personal sovereignty. Although there were no differences between cultures on the main PS score, we did find different PS patterns within all three cultures and when comparing males versus females. The PS scores in youth were higher than in adolescents, except in Armenia where the results were inverted. All age trends in PS were found in females, but not in males. Gender differences in PS within each culture were found in youth but not in adolescents. Conclusion. We discussed and explained the outcomes with reference to the specificity of the way each culture endorses traditional or secular-rational values, which values determine the prevalent attitudes towards gender roles and demands on adolescents and youth.